Perceptual-Motor Deficits and Congenital MD - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1995)
Fine motor and perceptuo-motor abilities in 22 children with congenital muscular dystrophy, with and without MRI changes, were evaluated at the Hammersmith Hospital, London, UK.